A and B site doping of a phonon-glass perovskite oxide thermoelectric - Daniels, L.M.; Ling, S.; Savvin, S.N.; Pitcher, M.J.; Dyer, M.S.; Claridge, J.B.; Slater, B.; Corà, F.; Alaria, J.; Rosseinsky, M.J. (Royal Society of Chemistry, 2018)
By tuning the A site cation size it is possible to control the degree of octahedral distortion and ultimately structural symmetry in the new perovskite solid solution La0.5Na0.5−xKxTiO3, affording a rhombohedral-to-cubic transition as x increases above 0.4. The La3+ and K+ cations are distributed randomly across the A site leading to significant phonon disorder in cubic La0.5K0.5TiO3 (Pm[3 with combining macron]m) which produces a phonon-glass with a thermal conductivity of 2.37(12) W m−1 K−1 at 300 K; a reduction of 75% when compared with isostructural SrTiO3. This simple cation substitution of Sr2+ for La3+ and K+ maintains the flexible structural chemistry of the perovskite structure and two mechanisms of doping for the introduction of electronic charge carriers are explored; A site doping in La1−yKyTiO3 or B site doping in La0.5K0.5Ti1−zNbzO3. The phonon-glass thermal conductivity of La0.5K0.5TiO3 is retained upon doping through both of these mechanisms highlighting how the usually strongly coupled thermal and electronic transport can be minimised by mass disorder in perovskites. Precise control over octahedral distortion in A site doped La1−yKyTiO3, which has rhombohedral (R[3 with combining macron]c) symmetry affords lower band dispersions and increased carrier effective masses over those achieved in B site doped La0.5K0.5Ti1−zNbzO3 which maintains the cubic (Pm[3 with combining macron]m) symmetry of the undoped La0.5K0.5TiO3 parent. The higher Seebeck coefficients of A site doped La1−yKyTiO3 yield larger power factors and lead to increased thermoelectric figures of merit and improved conversion efficiencies compared with the mechanism for B site doping.